2013
DOI: 10.1155/2013/161687
|View full text |Cite
|
Sign up to set email alerts
|

Early Alzheimer’s and Parkinson’s Disease Pathology in Urban Children: Friend versus Foe Responses—It Is Time to Face the Evidence

Abstract: Chronic exposure to particulate matter air pollution is known to cause inflammation leading to respiratory- and cardiovascular-related sickness and death. Mexico City Metropolitan Area children exhibit an early brain imbalance in genes involved in oxidative stress, inflammation, and innate and adaptive immune responses. Early dysregulated neuroinflammation, brain microvascular damage, production of potent vasoconstrictors, and perturbations in the integrity of the neurovascular unit likely contribute to progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 124 publications
(196 reference statements)
2
75
0
1
Order By: Relevance
“…In the setting of severe air pollution, a serious concern is vitamin D deficiency in close association with indoor confinement during the day, residency at higher altitudes, darker skin pigmentation and poor nutritional intake (Alvaer et al, 2007;Balasubramanian and Ganesh, 2008;Calderón-Garcidueñas et al, 2013a, 2013bChristakos et al, 2013;Kelishadi et al, 2014;Miñ-ambres et al, 2014). Vitamin D deficiency in Metropolitan Mexico City area (MCMA) children is important because well-known metabolic and dementia links (Annweiler et al, 2013;Anastasiou et al, 2014;Bishnoi et al, 2014;Bartali et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the setting of severe air pollution, a serious concern is vitamin D deficiency in close association with indoor confinement during the day, residency at higher altitudes, darker skin pigmentation and poor nutritional intake (Alvaer et al, 2007;Balasubramanian and Ganesh, 2008;Calderón-Garcidueñas et al, 2013a, 2013bChristakos et al, 2013;Kelishadi et al, 2014;Miñ-ambres et al, 2014). Vitamin D deficiency in Metropolitan Mexico City area (MCMA) children is important because well-known metabolic and dementia links (Annweiler et al, 2013;Anastasiou et al, 2014;Bishnoi et al, 2014;Bartali et al, 2014).…”
mentioning
confidence: 99%
“…The APOE ε4 allele is the strongest known genetic risk factor for late and early onset AD (Michaelson, 2014;Huang and Mahley, 2014), and given our previous reports of Mexico City APOE 4 young carriers accelerating their expression of AD neuropathological markers (Calderón-Garcidueñas et al, 2008a, 2008b, 2010, 2012a, 2012b, 2013a, 2013b, APOE genotyping was included in this work. Likewise, high concentrations of endothelin-1 (ET-1), a marker of endothelial dysfunction and exposure to severe air pollution obligated its inclusion (Calderón-Garcidueñas et al, 2007).…”
mentioning
confidence: 99%
“…Finally, the presence of nanoparticulate matter in such environments may also be a source of neuropathology per se whether coated in mycotoxins or not [313,314]. These authors have demonstrated that such nanoparticles passage into the brain via the olfactory epithelium and the olfactory bulb lead to increased production of inducible nitric oxide synthase (iNOS), NF-ΚB, and TNFα and the deposition of beta amyloid plaques highly reminiscent of the pattern seen in Alzheimer's disease [314,315]. These authors also reported the results of a disturbing study examining the effects of the polluted air of Mexico City on the brains of local children.…”
Section: Chronic Mold and Mycotoxin Exposurementioning
confidence: 99%
“…Так, одним из первых симптомов развития ряда деменций (болезнь Паркинсона, болезнь Альцгей-мера и др.) является нарушение восприятия запаховых стимулов, поэтому воздействия факторов среды, в том числе компонентов вдыхаемых аэрозолей, рассматривают в качестве возможных экологических факторов риска для данных заболеваний (CalderónGarcidueñas et al, 2013).…”
unclassified